2008
DOI: 10.1111/j.1349-7006.2008.00874.x
|View full text |Cite
|
Sign up to set email alerts
|

TUSC4/NPRL2, a novel PDK1‐interacting protein, inhibits PDK1 tyrosine phosphorylation and its downstream signaling

Abstract: 3-Phosphoinositide-dependent protein kinase-1 (PDK1) is a key regulator of cell proliferation and survival signal transduction. PDK1 is known to be constitutively active and is further activated by Srcmediated phosphorylation at the tyrosine-9, -373, and -376 residues. To identify novel regulators of PDK1, we performed E. coli-based two-hybrid screening and revealed that tumor suppressor candidate 4 (TUSC4), also known as nitrogen permease regulator-like 2 (NPRL2), formed a complex with PDK1 and suppressed Src… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 30 publications
3
20
0
Order By: Relevance
“…miR-409-5p has been shown to target STAG2, RSU1, NPRL2 and RBL2 (12). NPRL2 activates AKT pathway (39, 40) and RBL2 activates the E2F pathway (41). Thus, these miRNA activate oncogenic proteins by targeting tumor suppressors.…”
Section: Resultsmentioning
confidence: 99%
“…miR-409-5p has been shown to target STAG2, RSU1, NPRL2 and RBL2 (12). NPRL2 activates AKT pathway (39, 40) and RBL2 activates the E2F pathway (41). Thus, these miRNA activate oncogenic proteins by targeting tumor suppressors.…”
Section: Resultsmentioning
confidence: 99%
“…Growth factor stimulation leads to sequential phosphorylation of Tyr 9 and Tyr 373/376 (11,14,16,17), and substitutions for these phosphotyrosines result in decreased PDK1 activity (9,13,14,16,47). Previous studies showed that Pyk2 activates PDK1, but the mechanism was not determined (9,12,18).…”
Section: Discussionmentioning
confidence: 99%
“…It may be possible that the NPRL2/3 human analogs perform similar functions to the yeast NPR2/3 proteins in conveying the amino acid signal to mTORC1. Interestingly, a recent study by Kuruta et al (57) demonstrated that NPRL2 interacted with and inhibited PDK1 (phosphoinositide-dependent kinase-1). PDK1 is upstream of the Akt/mTORC1 pathway (see Fig.…”
Section: Npr2 and Npr3mentioning
confidence: 96%